Occasional papers in language and literature - Radhakrishna Budaraju (Hyderabad Prachee publications, 1998)
This collection relates to some theoretical discussions with special reference to Telugu grammar, dialectical balance, terminological problems, linguistics & etymology bearing on sociolinguistic aspects.
Keywords: Telegu language